Monitoring, evaluation, accountability, and learning (MEAL) in anticipatory action—earth observation as a game changer - Enenkel, Markus; Dall, Karen; Huyck, Charles K.; McClain, Shanna N.; Bell, Veronica (Frontiers in Climate, 2022)
For many decades, humanitarian assistance relied on emergency response, triggering both funding and operational activities only after disaster impacts had been recorded. In recent years, many humanitarian actors have joined forces to complement traditional, reactive mechanisms with a forward-looking approach that can be activated before a disaster strikes. Anticipatory action (AA) uses forecasts of extreme weather events and combines them with risk information to identify and implement locally-led early actions with the goal of protecting lives and livelihoods more efficiently. AA is still a relatively new approach. Hence, monitoring, evaluation, accountability and learning (MEAL) is crucial to measure its effectiveness and adjust where necessary, as well as for (government) donors that want to see the added value of their investment maximized. However, evidence-based studies that investigate potential limitations and the exact impact pathway of AA at household level are time-consuming, costly, and therefore scarce. Satellite earth observation can become a game changer in AA by strengthening the evidence base via rapid, low-cost assessments. Both commercial and freely available satellite-derived data have reached an unprecedented level of quality, spatial, and temporal resolution. Simultaneously, there are major uncertainties regarding where, when, how, and under what conditions satellite data can support MEAL for AA at all. We argue that satellite data for an advanced MEAL framework should be considered already in the design phase of AA projects and that the translation of satellite data into actionable information will require a cross-cutting community of practice.